Kesesuaian Prosedur Pinjaman Online dengan Maqashid Syariah - Jamudi, Jamudi; Fatimah Hasibuan, Sri; Hasibuan , Abdul Nasser (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the compliance of Islamic-based online loan procedures with the principles of Maqashid Syariah. A qualitative normative-juridical approach was employed through literature analysis of OJK regulations, DSN-MUI fatwas, and both classical and contemporary maqashid theories. The findings indicate that most Islamic fintech lending platforms in Indonesia have implemented maqashid syariah values, particularly in terms of justice, transparency, and asset protection (hifz al-mal). However, challenges remain in the transparency of service fees and consumer understanding of contract mechanisms, which may raise concerns of hidden interest practices. The originality of this research lies in its procedural analysis of Islamic fintech from the maqashid perspective rather than mere legal compliance. Its innovation highlights the integration of digital financial technology with maqashid-based design principles. The study’s implications emphasize the importance of enhancing regulation, Islamic financial literacy, and digital sharia audit to ensure a fair and ethical Islamic online lending ecosystem.